Preparation, Characterization and Compatibility Studies of Naproxen Loaded Microspheres of Cellulosic and Polymethacrylic Polymeric Blend - Akhter, Sharmin; Paul, Shova; Hasan, Ikramul; Ayon, Navid Jubaer; Haider, Syed Shabbir; Reza, Md. Selim (Dhaka University Journal of Pharmaceutical Sciences, 2013)
Naproxen, a well-known non-steroidal anti-inflammatory drug was encapsulated with cellulosic and polymethacrylic polymers to provide sustained action and to minimize gastro esophageal side effects by avoiding the release of drug in the upper gastrointestinal tract. Emulsification-solvent evaporation technique using Ethyl Cellulose, Eudragit RSPO and their combination as release retardant was the method of choice. The formulations were prepared by keeping the amount of drug fixed to 1g and the total amount of polymer fixed to 1g in which Ethyl Cellulose and Eudragit RSPO were used in varying combination. In-vitro drug release was studied in a paddle type dissolution apparatus (USP type II) for eight hours in phosphate buffer having pH 7.4. After 8 hours, the release of drug was 86.20% for F6 which contains equal amount of Ethyl Cellulose and Eudragit RS PO and 71.57% for F7 which contains only Eudragit RSPO. The release mechanisms were explored and explained with zero order, first order, Higuchi, Korsmeyer-Peppas and Hixson Crowell models. The correlation-coefficient values of the trend lines of the graphs showed that the formulations were best fitted with Korsmeyer-Peppas release pattern. Microspheres surface morphological study was done by Scanning Electron Microscopy (SEM). Drug polymer incompatibility studies were performed by Differential Scanning Calorimetry (DSC) and Fourier Transform Infrared Spectroscopy (FTIR). The absence of endothermic melting peak of Naproxen in DSC thermogram revealed that the drug might be dispersed in the polymer as solid solution or in a metastable molecular dispersion. But the chemical integrity of Naproxen was not changed or destroyed within the microsphere which was confirmed by FTIR report. Dhaka Univ. J. Pharm. Sci. 12(1): 11-21, 2013 (June) DOI: http://dx.doi.org/10.3329/dujps.v12i1.16295